Kompetensi Kepribadian Guru Dalam Pembentukan Karakter Siswa di SDN Unggulan 1 Kabupaten Pulau Morotai Provinsi Maluku Utara - Timbuleng, Nilla; Lengkong, Jeffrey; Dapa, Aldjon Nixon (Peneliti.net, 2023)
The aim of this research is to obtain data, analyze and describe teacher personality competencies in forming student character at SDN Unggulan 1 Morotai Island Regency. By using qualitative methods, in this research process, researchers will be at the research location to communicate with various parties, including teachers, students, school principals and parents to obtain the data needed for this research. Primary data can be obtained through interviews with the principal, teachers, school committee, parents/guardians of students. Data collection techniques are carried out by means of observation, interviews and documentation. From the results of this research it can be concluded that 1) Teacher personality competence plays an important role in creating an educational environment that supports and encourages student character formation. 2) Through this combination of personality competencies, a teacher can create an environment that supports, inspires and shapes students' characters with positive values. 3) By deeply understanding their roles and responsibilities, teachers can create more effective, relevant and meaningful educational experiences for students. 4) Teachers with personality competencies that are in line with the school's values and vision can help create consistency in workforce management. 5) Teachers who understand and apply the concept of empowerment can contribute to better staff development. towards change and encouraging innovation in educational practice. 6) Teacher Personality Competencies in Forming Student Character, can be carried out optimally at SDN Unggulan 1, Morotai Island Regency, North Maluku Province